DO TRUST AND CUSTOMER INTIMACY AFFECT CUSTOMER LOYALTY? - Farasky, Agung; Rusliyana Sari, Wahyuni; Pratomo, Luki Adiati (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2024)
This study aims to identify factors influencing customer loyalty in Islamic Banking customers. One hundred seventy respondents filled out the questionnaire online. The sample collection techniques were purposive sampling and the Structure Equation Model (SEM). The results indicated that customer trust and intimacy positively affect customer loyalty.